DETERMINAN KEBIJAKAN DIVIDEN PADA BIDANG KESEHATAN YANG TERDAFTAR DI BEI TAHUN 2016-2020 - Vivian Puspasari; Riana Rachmawati Dewi; Anita Wijayanti (ITB AAS INDONESIA, 2022)
Profit approach may be a approach that's chosen by the company's administration to choose whether the benefits earned by the company amid a period will be divided all or incompletely for profits and mostly not conveyed within the shape of held profit. The reason of this think about was to decide and analyze the impact of dividend approach determinants (administrative proprietorship, obligation arrangement, firm estimate, and free cash stream) within the wellbeing segment. Examining in this consideration utilized purposive testing. The test companies in this think about measured to 10 companies that met the testing criteria. Specialized investigation of the information utilized in this inquire about is to utilize numerous straightinvestigation.The comes.about of.this consider show that.the factors of administrative possession, obligation arrangement, and firm estimate have an impact on profit approach. Where as the free cash stream variable has no impact on profit policy. Keywords : Managerial Ownership, Debt Policy, Company size, Free Cash Flow, Dividend Policy